the strategy impact of guiding thinking through reading in questioning text among middle school students second grade (Journal of the College of Basic Education, 2022)
The current research aims to identify: (the strategy impact of guiding thinking through reading in questioning text among middle school students second grade). The current research is determined by the average second graders in the day middle or high school of the General Directorate of Education in the governorate of Baghdad, Rusafa / 3 The researcher followed an experimental design with partial control for the three research groups appropriate to the conditions of the current research. The research, and the mentioned medium included five divisions for the second intermediate grade, and by the method of random drawing, Division (C) was randomly chosen to represent the first experimental group, , and (E) to represent the control group, and the research sample reached (60) students by (30) in the experimental group, , and (30) students in the control group. After the researcher determined the scientific subject that he will study in the experiment, which is six topics from the book of reading and texts for the second intermediate grade, which is to be taught for the academic year (2019-2020), and in light of the content of these topics, the researcher prepared the necessary teaching plans for them by (6) plans to teach using a strategy Direct guiding thinking through reading, , and (6) plans to teach using the traditional method. to achieve the goal of the research, the researcher prepared test to measure the questioning of the text consisting of (35) paragraphs, from the type of substantive questions After analyzing the results of students answers and statistically processing them using the second test to find out the significance of the difference at the (5,05) level between the two Research group,it is clear what: there is a statistically significant difference between average (questioning) scores for students of the two research groups, and for the benefit students of the experimental group who they studied reading material(the strategy of guding thinking though reading).In the light of the research results, the researcher concluded a number of conclusions, including: That use strategy of guiding thinking through reading in teaching reading material impact positive increasing capacity Students intermediate second grade on interrogating texts. The researcher recommendedThe necessity of training and encouraging male and female teachers by the Ministry of Education to follow modern teaching methods and strategies based on constructive theory in which the student is at the center of the educational process, including strategie guiding thinking through reading.